2010
DOI: 10.1093/nar/gkq434
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and structural properties of YOYO-1 complexed DNA

Abstract: YOYO-1 is a fluorescent dye widely used for probing the statistical–mechanical properties of DNA. However, currently contradicting data exist how YOYO-1 binding alters the DNA structure and rigidity. Here, we systematically address this problem using magnetic tweezers. Remarkably, we find that the persistence length of DNA remains constant independent of the amount of bound YOYO-1, which contrasts previous assumptions. While the ionic conditions can considerably alter the stability of YOYO-1 binding, the DNA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
247
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(268 citation statements)
references
References 23 publications
20
247
1
Order By: Relevance
“…In the presence of DNA intercalators, however, it is known that elongation of double DNA requires less force. For example, recent experiments showed that the presence of a YOYO-1 force of a few picoNewtons could elongate DNA contour by approximately 1.5-fold (36). Although the structure of the nonhysteretic overstretched DNA remains unknown, we imagine that DNA bound with YOYO-1 may resemble the DNA structure because it is only 10% shorter.…”
Section: Discussionmentioning
confidence: 95%
“…In the presence of DNA intercalators, however, it is known that elongation of double DNA requires less force. For example, recent experiments showed that the presence of a YOYO-1 force of a few picoNewtons could elongate DNA contour by approximately 1.5-fold (36). Although the structure of the nonhysteretic overstretched DNA remains unknown, we imagine that DNA bound with YOYO-1 may resemble the DNA structure because it is only 10% shorter.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies of DNA extension under dynamic conditions, such as in flow 49 or electrokinetic stretching around solid obstacles, 50,51 suggest that the backbone length should increase by 25% to 30% at full dye loading, corresponding to an increase from the naked contour length of 16.5 μm, based on a rise of 0.34 nm per base pair, to a stained contour length around 22 μm. 37 At the dye to base pair ratio used here of 1:10, others 4,43 suggested that the increased contour length due to dye intercalation is approximately 19.8 μm. Alternatively, if we assume that the increase in the backbone length is linear in dye loading up to the maximum loading, then the 40% loading we used here should lead to a dyed contour length of L = 18.3 μm.…”
Section: B Comparing Simulation and Experimentsmentioning
confidence: 90%
“…The intercalating dyes in these experiments introduce an additional unknown parameter, the contour length in the presence of the dye. Although many studies have investigated the physical properties of DNA in the presence of these dyes, 34,43,44 there exists a lack of consensus on how l p and w vary as a function of dye concentration. Therefore, we chose the simplest approach and estimated the parameters, l p and w using established theories [29][30][31] for undyed DNA.…”
Section: B Parameter Estimationmentioning
confidence: 99%
“…In some cases, the prefactors for the scaling laws are known exactly [41][42][43]. These thermodynamic quantities depend on the contour length L of the polymer, its persistence length l p , the effective width w of the polymer backbone, and the channel size D. The persistence length and effective width of DNA, which are affected by the relative amount of screening of electrostatics by the ionic environment, can be obtained from polyelectrolyte theory [44][45][46][47], albeit with some uncertainty arising from the effect of the intercalating dye [48][49][50][51][52][53][54]. Intercalation also increases the DNA contour length relative to the rise of naked DNA [55].…”
Section: Introductionmentioning
confidence: 99%